Association of Brain Iron Overload With Brain Edema and Brain Atrophy After Intracerebral Hemorrhage - Liu, Ran; Zhang, Haoran; Cheng, Shuangjuan; Sun, Yuyao; Li, Haijiao; Xiao, Jiangxi; Huang, Yining (Frontiers in Neurology, 2020)
Objective: Our study evaluated the iron overload after intracerebral hemorrhage (ICH) using ESWAN sequences. Methods: This study was a single-center prospective observational cohort study enrolling supratentorial ICH patients. MRI was obtained with a 3.0-T scanner at day 1, day 14, day 30 and follow-up (300 days or later). R2* mapping was generated based on ESWAN. R2* value of ipsilateral side represented iron deposition, and R2* value of contralateral side served as control. R2* value adjusted by volume was used to assess total iron overload. Brain edema was measured on T2 FLAIR-weighted images. Brain atrophy was calculated as the contralateral hemisphere volume minus the injured hemisphere volume. Results: 27 patients with a spontaneous? supratentorial ICH were included in this analysis. The ipsilateral R2* value was 40.27 ±11.62, 41.92± 13.56, and 60.89±14.09 at day 1, 14, and 30, respectively. The R2* value was significantly higher in the ICH side than the contralateral side (p<0.01). Increased R2* value was seen in day 30 compared to day 14(p<0.01). The R2* value showed logistic decay with the distance to hematoma margin (p<0.01). Brain edema at day 14 and brain atrophy at follow-up correlated with R2* value adjusted by volume at day 14 (p<0.01). Conclusions: After ICH, the iron deposition in the peri-hematoma region was progressively increased during the first month. R2* value adjusted by volume predicted acute brain edema and chronic brain atrophy.